The affecting factors of choosing delivery place in Working Area of Sikumana Health Center - Maria Vilastry Nuhan; Roslin E Sormin; Mardiana S Bhoko (Alma Ata University Press, 2021)
Background: One of the causes of maternal and infant mortality is childbirth that still occurs at home with inadequate health facilities. Delivery at adequate health care facilities can reduce Mother Mortality Rate and Infant Mortality Rate. Objectives: This study aims to analyze the effect of antenatal care, family support and health support of workers regarding a place of delivery choice based on the MCH Revolution in working area of Sikumana Health Center, Kupang. Methods: This study used a case control design. The sample size of the case group was 30 women who gave birth in non-adequate health facilities and the control group was 30 women who gave birth in adequate health facilities. The sample collected by random sampling technique and used direct interview and questionnaire. Data analysis was carried out using Chi Square statistical test. Results: The results of the analysis indicated that from the studied variables, variables that influenced the choice of labor place were the mother's attitude (p = 0.000), and the history of previous place (p = 0.038), while the variable of mother's age did not affect (p = 0.778). Conclusion: The mother's attitude and previous delivery history had an effect on the choice of labor place, while the mother's age did not have any effect. These risk factors are expected to be a special concern for health workers in providing counseling for pregnant women in determining the place of labor. In addition, intense support from health workers is needed to motivate mothers and families to choose adequate health facilities as a place of labor.